On surface enhancement using viscoelastic abrasive laden media in rotary ultrasonic finishing process - Mun, Wai Hoong (2019)
Rotary Ultrasonic Machining (RUM) is a technique combining diamond grinding and ultrasonic vibrations to drill holes with superior surface finishing. It can reduce the number of cracks, tearing defects and subsurface damages as compared to traditional drilling processes. This technique is especially successful with materials that are hard and brittle due to the low cutting forces and thus play a pivotal role in manufacturing process of precise parts across various industry. This research aims to develop a non-contact surface finishing technique – Rotary Ultrasonic Finishing Process (RUFP). In this report, experimental investigation will be conducted on the effects of key input parameters including ultrasonic frequency, amplitude of vibration and rotational speed on the output parameters including surface roughness arithmetic average (Ra), sum of the average five highest peaks and five lowest valleys of the profile from the mean line (Rz) and material removal rate (MRR) on aluminium alloy (Al 6061). The experiments in this study have shown improvements in surface finish. Rougheness parameters Ra and Rz have found to decrease up to 10 % for as compared to less than 1 % decrease for non-rotary ultrasonic finishing. Surface finishing has shown improvement when frequency is decreased from 40 kHz to 20 kHz, amplitude is increased from 6 μm to 60 μm and rotational speed is decreased from 3000 rpm to 2500 rpm. It can be concluded that the possibility of a non-contact Rotary Ultrasonic Finishing Process is a promising technique with results showing the improved surface finished. However, this study is limited to the use of silicon carbide abrasive of size 150 μm to 220 μm at 60% concentration. Further investigation can be carried by varying parameters such as abrasive type and size, concentration of abrasives slurry and feed rate before its application into more complex processes.